Comparison of Various Kangaroo Mother Care Carriers on Maternal Comfort: A Pilot Study. (30th November 2017) - Amaliya, Sholihatul; Rustina, Yeni; Agustini, Nur
ABSTRACT: Kangaroo mother care (KMC) is an evidence-based approach that has been scientifically proven to have a positive effect on mothers and infants. One of the barriers to performing KMC at home is the absence of a special KMC carrier. The most widely used KMC carriers in Indonesia are kangaroo pouch, thari, wrap and traditional wraps in the form of a long strip of fabric. This study's aim was to compare the level of maternal comfort when performing KMC with three different KMC carriers. The study used crossover design involving 20 mothers with low birth weight (LBW) infants as responders, selected through a consecutive sampling method. Data were collected using a maternal comfort questionnaire, maternal anxiety questionnaire, and KMC observation sheet. The results of repeated analysis of variance (ANOVA) showed that there was no significant difference in maternal comfort when performing KMC with any of three KMC carriers (maternal comfort p  = .366, α  = .05). Therefore, KMC can be implemented using any of the types of carriers including kangaroo pouch, thari wrap, and traditional wrap.